2005
DOI: 10.1002/adfm.200400333
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of Vaterite Nanowires by the Cooperative Interaction of Tailor-Made Nucleation Surfaces and Polyelectrolytes

Abstract: The concepts of template‐induced crystallization on self‐assembled monolayers (SAMs) and the use of polymer additives are combined into a new strategy, where, through the cooperative interaction of a SAM matrix involved in the nucleation process, poly(acrylic acid), a dissolved polyelectrolyte, and the dissolved ions, hierarchically ordered mineral structures are formed. The adsorption of poly(acrylic acid) to the SAM is monitored using a quartz microbalance. Transmission electron microscopy measurements on sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
56
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 42 publications
3
56
0
Order By: Relevance
“…49 Therefore, the final ACC particles were formed by the aggregation of nanosized ACC precursors. The amorphous precursors would transform to vaterite or calcite nanocrystallites with decreasing inhibiting efficiency of PAA-Na in the lower ratios of [-COO À ]/[Ca 2þ ], and the final crystal particles were also formed by the aggregation of nanocrystallites.…”
Section: Discussionmentioning
confidence: 99%
“…49 Therefore, the final ACC particles were formed by the aggregation of nanosized ACC precursors. The amorphous precursors would transform to vaterite or calcite nanocrystallites with decreasing inhibiting efficiency of PAA-Na in the lower ratios of [-COO À ]/[Ca 2þ ], and the final crystal particles were also formed by the aggregation of nanocrystallites.…”
Section: Discussionmentioning
confidence: 99%
“…The control of the crystal growth features of inorganic materials has become an active research field in the last two decades, because of the increasing interest in obtaining materials with homogeneity and specificity of both the crystal shape and the size distributions, key aspects in many applications. [4,5] This scientific interest has focussed on a limited number of systems, among which the most important are carbonates [6][7][8] (calcium and barium carbonate), phosphates [9,10] (calcium and zinc phosphates), sulfates [11] (barium sulfate), sulfides [12][13][14][15][16] (zinc and cadmium sulfide), chromates, [17] and several metal oxides [18][19][20] (aluminum, zinc, titanium, zirconium, and iron oxides). From the mechanistic point of view, zinc oxide is quite an ideal system for studies of the controlled crystallization.…”
Section: Introductionmentioning
confidence: 99%
“…Calcium-induced bundle formation of polyacrylate fibers on carboxylate-terminated SAMs was reported by Tremel and co-workers. [51] In the presence of carbon dioxide vapors, the MOPF bundles template the nucleation, the growth, and the assembling of calcite microcrystals (Figure 3). The biomineralization experiments were carried out by using the diffusion method in a closed dessicator.…”
mentioning
confidence: 99%
“…Calcite microcrystals have been grown on a wide variety of templates, including Kevlar, [54][55][56] nylon, [57] self-assembled monolayers, proteins, etc. [51,[58][59][60][61][62][63][64][65][66][67][68] Reminiscent of collagen processing, [69] the approach delineated herein represents an example of hierarchical self-assembly in which each stage involves building blocks of increasing size such that the resulting supramolecular structure spans over six orders of magnitude, from nanometer-sized covalent building blocks to millimeter calcite wires. [70] We have demonstrated that streptavidin (the linker) combined with a linear tetrabiotinylated connector, the [Fe(Biot 2 -terpy) 2 ] 2+ complex, spontaneously self-assemble into a one-dimensional metal-organic protein framework.…”
mentioning
confidence: 99%